Faktor yang Berhubungan dengan Perilaku Berisiko Anemia pada Remaja Putri di SMK Pariwisata Imelda Medan Tahun 2025 - Sari Siregar, Dian Maya; Agustina, Winda; Gea, Limse Niat; Januariana, Neni Ekowati (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Introduction: Anemia is a nutritional problem worldwide, including in Indonesia. Adolescent girls are more prone to anemia, which can have both short-term and long-term negative impacts on their health, productivity, and readiness to become future mothers. The World Health Organization (2023) reported that the global prevalence of anemia among women aged 15–49 years is 30%. The North Sumatra Provincial Health Office (2023) stated that the prevalence of anemia among adolescent girls is 65.32%. Objective: To determine the factors associated with anemia risk behavior among adolescent girls at SMK Pariwisata Imelda Medan. Materials and Methods: This study employed a quantitative design with a cross-sectional approach. The population consisted of all female students in grades X and XI, totaling 406 individuals. A sample of 201 respondents was selected using stratified random sampling. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test. Results: The study showed a significant association between knowledge, attitudes, sources of information, and teacher roles with anemia risk behavior among adolescent girls, with p-values of 0.00 < α = 0.05. Meanwhile, parental roles were not associated with anemia risk behavior among adolescent girls, with a p-value of 0.073 > α = 0.05. Conclusion: There is a significant relationship between knowledge, attitudes, sources of information, and teacher roles with anemia risk behavior among adolescent girls, whereas parental roles have no relationship with anemia risk behavior in adolescent girls.